(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Objectives: The term "transient ischemic dilation" (TID) refers to the apparent significant enlargement of left ventricle (LV) on post-stress images as compared to rest images on SPECT radionuclide myocardial perfusion imaging (MPI). In presence of abnormal SPECT MPI, transient ischemic dilatation (TID) is regarded as a sign of severe and widespread coronary artery disease (CAD) with poor prognosis. However, high TID is also observed with normal MPI. The possible explanations are balanced epicardial CAD, diffuse microvascular disease or widespread subendocardial ischemia which would be associated with adverse outcomes. TID has been identified as a significant indication of severe and widespread CAD and predictive of a high risk of cardiac events. However, the clinical relevance of TID and its relationship with CAD in individuals with an otherwise normal MPI exam is unknown. Patients & Methods: This observational study was conducted in Nuclear Cardiology division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS), BSMMU campus, Dhaka from January 2023 to December 2023. Out of a total of 178 patients who underwent stress-rest SPECT-MPI in the nuclear cardiology division, ten patients were identified with normal perfusion scans but exhibited high TID values. The TID index was calculated based on published threshold values with >1.12 denoting high TID. Almost all the patients went through coronary angiogram (CAG) within six months and had positive findings. This study aimed to investigate the relationship between TID and the presence or severity of coronary artery disease (CAD) in angiography. Results: Among the ten patients having normal perfusion but high TID, there is male predominance. Age ranges from 34 to 74 years. Nine out of ten patients had undergone previous coronary angiography (CAG) within a six-month timeframe, revealing triple vessel disease (TVD) in five patients (50%), double vessel disease (DVD) in three patients (30%), and single vessel disease (SVD) in one patient (10%). One patient did not have any CAG. The patients with TVD and two DVDs on CAG were obstructive CAD which was defined as diameter stenosis of 50% or more in the left main coronary artery or stenosis of 70% or more in a major epicardial vessel. The remaining patients were diagnosed with nonobstructive CAD based on angiogram findings. Conclusions: In this observational study, the clinical relevance of obstructive CAD is highlighted by the presence of high TID accompanied with otherwise normal SPECT MPI, which reveals the existence of CAD and predicts a significant risk of cardiac events. Bangladesh J. Nuclear Med. 28(1): 87-90, 2025